Impact of Technology Integration on Student Engagement in Secondary Schools in Mozambique - Ferreira, Raquel (Journal of Education and Practice, 2026)
Purpose: The purpose of this article was to analyze impact of technology integration on student engagement in secondary schools. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Technology integration in secondary schools is linked to increased student engagement, including higher motivation and participation. Studies show that interactive tools like digital platforms improve academic outcomes and foster greater classroom involvement. However, the impact varies based on factors like teacher training and technology access. Unique Contribution to Theory, Practice and Policy: Constructivist learning theory, the technology acceptance model (TAM) may be used to anchor future studies on the impact of technology integration on student engagement in secondary schools. In practice, it is essential that secondary school educators receive comprehensive and continuous professional development in integrating technology into their teaching. From a policy perspective, governments should prioritize investment in digital infrastructure to ensure equitable access to technology for all students, regardless of their socio-economic background.